Mengungkap Keterkaitan Inklusi dan Literasi Keuangan dengan Kinerja dan Keberlanjutan UMKM di Perkotaan - Ariyanti, Rina (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
Within the economic landscape of Depok City, the Micro, Small, and Medium Enterprises (MSMEs) sector holds a pivotal position, contributing significantly to the local economy. Despite its importance, a myriad of challenges confront MSMEs in the city, encompassing issues related to financial access and insufficient financial literacy. Consequently, this study seeks to empirically examine and elucidate the influence of financial inclusion and financial literacy, with business sustainability serving as an intermediary variable within the MSME sector of Depok City. Utilizing the Non-Probability sampling method, this research engaged MSME participants in Depok City, with a population of 7911, employing the Slovin formula to determine a representative sample size of 200. Employing the Partial Least Square- Structural Equation Modeling (PLS-SEM) method for data analysis, this quantitative research aims to contribute valuable insights to the existing body of knowledge. The findings reveal a discernible impact of Financial Inclusion on both the Performance and Sustainability of MSMEs. Similarly, Financial Literacy emerges as a significant factor influencing the Performance and Sustainability of MSMEs. Furthermore, Business Sustainability is identified as a mediating factor, demonstrating its capacity to mediate the relationship between Financial Inclusion and MSME Performance, as well as between Financial Literacy and MSME Performance. This study serves as a valuable reference for MSME stakeholders, underscoring the imperative nature of accessible banking services for optimal financial outcomes. The results advocate for enhanced financial literacy as a means to fortify the performance and sustainability of MSMEs. In conclusion, the study attests to the resilience of many MSMEs in Depok City, substantiating their ability to endure and thrive in their business endeavors, evident by a sustained operational existence exceeding five years.